Comparison of autoinjector with accessorized prefilled syringe for benralizumab pharmacokinetic exposure: AMES trial results. (2nd January 2021) - Martin, Ubaldo J.; Fuhr, Rainard; Forte, Pablo; Barker, Peter; Axley, Milton J.; Aurivillius, Magnus; Yan, Li; Roskos, Lorin
Abstract: Objective: We compared the pharmacokinetic exposure following a single subcutaneous dose of benralizumab 30 mg using either autoinjectors (AI) or accessorized prefilled syringes (APFS). APFS and AI functionality and reliability for at-home benralizumab delivery have been demonstrated in the GREGALE and GRECO studies, respectively. Methods: In the open-label AMES study (NCT02968914), 180 healthy adult men and women were randomized to one of two device (AI or APFS) and three injection site (upper arm, abdomen, or thigh) combinations. Randomization was stratified by weight (<70 kg, 70–84.9 kg, and ≥85 kg). Blood eosinophil counts were measured on Days 1, 8, 29, and 57. Results: Benralizumab pharmacokinetic exposure was similar between AI and APFS. Geometric mean ratios (AI/APFS) (90% CI) were 92.8% (87.4–98.6) and 94.5% (88.2–101.2) for two area under the concentration‒time curve measurements (AUClast and AUCinf ). Benralizumab exposure was approximately 15–30% greater for thigh vs. abdomen or upper arm administration. Exposure was slightly greater for APFS vs. AI regardless of injection site or weight class. These differences were unlikely to be clinically relevant, as eosinophil depletion was achieved consistently with both devices at all injection sites. No device malfunctions were reported. No new or unexpected safety findings were observed. Conclusion: Benralizumab pharmacokinetic exposure was similar between AI and APFS, with consistent blood eosinophil count depletion observed with both devices. These results support benralizumab administration with either AI or APFS, providing patients and physicians increased choice, flexibility, and convenience for potential at-home delivery.